Effect Of Genetic And Non-Genetic Sources Of Variation On Service Period In Gir Cows - Kumar, Amit; Tomar, S.S.; Sharma, Harish; Rajoriya, Ravi (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Effects of Inbreeding, sire, period and season of calving and parity on service period (SP) were studied on Gir cows maintained at the Kasturba Gandhi National Memorial Trust Dairy Farm, Kasturbagram, Indore (M.P.). A total of 542 observations of SP on 191 cows were included in the study. The service period in these cows averaged 182.58±9.13 days and was significantly affected by inbreeding (p
Keywords: Service period; Gir; inbreeding